HPLC determination of polydextrose in fortified milk - Veena, N; Surendra Nath, B (Indian Journal of Dairy Science, 2017)
Polydextrose, a soluble fibre, was used as a fortificant in milk. A HPLC method was standardized to estimate polydextrose in milk. The separation of lactose and polydextrose was achieved, on the filtrate obtained after removal of proteins and fat from milk. The chromatogram was run on a Hiplex calcium column (300x7.7 (i.d); 8 Î¼m film) and the separated components were detected on refractive index detector.Â  HPLC grade water was used as mobile phase at a flow rate of 0.5 ml/min. The polydextrose mass recovery ranged from 94.3% to 99.3% with a RSD of 2.68%. The method is found to be simple, reproducible and reliable, and thus ideally suitable for the analysis of polydextrose in food product.Â  The method also did not interfere with lactose present in milk, which also could be estimated in the same run.Â